Gram‐Scale Synthesis of Tomatidine, a Steroid Alkaloid with Antibiotic Properties Against Persistent Forms of Staphylococcus aureus. Issue 18 (30th April 2020) - Normandin, Chad; Malouin, François; Marsault, Eric
Abstract : We herein describe the first diastereoselective synthesis of the Solanum alkaloid tomatidine 1 . The synthesis has been accomplished in 11 steps and 24.9 % overall yield (longest linear sequence). This methodology, which involves a convergent synthon insertion followed by a sequence of ring opening/nitrogen substitution/ring closing, allowed the generation of 1 on > 2 g scale. The synthetic challenge with the diastereoselective generation of the unusual spiroaminoketal moiety was solved through a combined azide reduction/addition sequence. The first diastereoselective synthesis of the phytosteroid yamogenin is also reported. Tomatidine has shown promising antibiotic properties against persistent forms of Staphylococcus aureus ( S. aureus ) and methicillin‐resistant S. aureus (MRSA). In particular, it possesses the unique ability to kill persistent forms of S. aureus and MRSA while simultaneously potentiating the antibiotic efficacy of aminoglycoside antibiotics against wild type strains of the bacteria. Abstract : The first synthesis of the Solanum alkaloid tomatidine was achieved in 24.9 % (longest linear sequence) through addition of a chiral organolithium fragment to a protected dinorcholanic lactone derived from commercially available diosgenin. This approach enabled the multigram synthesis with the goal to support further studies of its antibiotic properties against persistent forms of Staphylococcus aureus .